Analysis of Nuclear Explosion Detection Capability of IMS Hydroacoustic Network - Yan Wang; Wei Tang; Zhehan Liu; Jian Li; Xiaoming Wang; Shiya Zou (Shock and Vibration)
The Comprehensive Nuclear Test Ban Treaty (CTBT) organization has established a hydroacoustic network to ensure the effective detection of nuclear explosions in the vast ocean and in the atmosphere over it in order to effectively guarantee the implementation of the treaty. To assess its effectiveness, according to the reciprocity of underwater acoustic field, this study employs the hydrophone position as the central sound source and utilizes the parabolic equation, along with seabed topography and sound velocity profile data, to estimate the transmission loss. Background noise levels of station evaluation are conducted by using historical data so as to estimate the underwater nuclear explosion sound source level via a passive sonar equation. Utilizing the full ship shock trial (FSST) results of the “Ford” aircraft carrier on June 18, 2021, as a case study, the detection capability of the HA10 station for nuclear explosions is investigated. Subsequently, the network’s overall detection capability was evaluated using the source level at 20 Hz corresponding to a 1 kiloton nuclear explosion yield as a reference. Findings indicate the network’s proficiency in identifying long-distance propagation signals, particularly those with high explosion source levels within the sound fixing and ranging (SOFAR) channel. The sensitivity analysis demonstrates the network’s ability to detect explosions smaller than 1 kg equivalent in close proximity to a station, and larger explosions exceeding 1 kg or 1 ton at greater distances. This evaluation underscores the network’s significance in detecting and monitoring underwater nuclear explosions across extensive oceanic regions.